Comparison of As-Built Surveys Using Handheld Laser Scanner and Conventional Method - Yong Chun Yuan, Alister; Mohd Ariff, Mohd Farid; Omar, Abdullah Hisham; Mat Amim, Zulkarnaini (Journal of Advanced Geospatial Science & Technology, 2024)
With the advent of laser scanners in general, handheld laser scanners have become a tool used by surveyors to capture point clouds. The handheld laser scanner is useful for tight and confined spaces where a terrestrial laser scanner or a human cannot enter. Many surveyors still rely on the conventional method, which involves using a distometer and measuring tape for their strata as-built surveys. This is due to the simplicity and cost-effectiveness of the equipment. However, the conventional method is highly susceptible to human errors, unlike the laser scanner, which captures all features in point clouds without human intervention. In this research, data collected from both handheld laser scanners and conventional methods are compared. The handheld laser scanner captured a total of three levels. After collecting data at the site, the GeoSLAM Hub software processed the point clouds. This software helps convert the 3D point clouds into a 2D plan, with dimensions listed for the subsequent comparison process. The comparison focuses on the X and Y dimensions of the unit, with a tolerance of ±0.1m as per the circular KPUP-1-2015-JILID-I-v2016 provided by JUPEM. Following the comparison, the Root Mean Square Error (RMSE) is determined, with the lowest and highest values being 0.018m and 0.024m, respectively. In conclusion, the results show a minimum difference of 0.001m and a maximum difference of 0.049m, which falls within the provided tolerance. The handheld laser scanner offers visual aids to surveyors, enabling them to identify discrepancies' locations quickly. However, its drawback lies in the equipment's cost. Ultimately, the strata as-built plan is prepared for the three surveyed levels.